Music as poetry and performance : arranged marriages, past instabilities, and Razak Abdul Aziz’s musical performance - Mohd Fairuz Zamani; Mohd Muzhafar Idrus (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines the intersection of music and literature by taking Malaysian musical performance song cycles as examples. The term, song cycles, is often used in musico-literary studies and is usually associated with Cyrus Hamlin and his definition of it as arrangements and reinterpretations of well-established literary narratives. By incorporating poetry analysis and interviews with Razak Abdul Aziz concerning his musical performance of 10 Pantun Settings, song cycles are recontextualised to incorporate vestiges of cultural identities, specifically, the notion of arranged marriages. As such, the article focuses on Razak Abdul Aziz’s musical performance of 10 Pantun Settings as he relates his musical experiences across interviews and the consciousness of the song cycle meanings. The article concludes that the fleeting musico-literary works of 10 Pantun Settings as musically composed and performed revealed the pervasiveness of dreariness, displacement, and disappointment across arranged marriages that provides real-life snapshots of loss and, to a certain extent, a vivid description of bereavement and grief from a “death of a marriage.” It is argued that through a complex rendering of arranged marriages, 10 Pantun Settings as a song cycle provoked a nostalgic saudade, past instabilities of what it means growing up married in preconfigured environments. Finally, this article references both the interviews and textual analysis of 10 Pantun Settings to the social exchange principles, specifically the consequence of the woman’s emotion in the arranged marriage.